Case report: Persistent hypogammaglobulinemia in thymoma-associated myasthenia gravis: the impact of rituximab or Good's syndrome? - Ren, Jingru; Wang, Jianchun; Liu, Ran; Guo, Jing; Yao, Yan; Luo, Jingjing; Hao, Hongjun; Gao, Feng (Frontiers in Neurology, 2023)
Introduction: Rituximab (RTX) showed good efficacy and safety for patients with myasthenia gravis. However, the percentage of peripheral CD20+ B cell may be absent for years after low dose of RTX treatment. Persistent hypogammaglobulinemia and opportunistic infection may occur in patients under treatment of RTX with thymoma relapse. Case representation: We report a case of refractory myasthenia gravis. After two doses of 100 mg rituximab, the patient developed transient neutropenia. The peripheral blood CD20+ B cell percentage was 0 more than three years. 18 months later, the patient’s symptoms relapsed with thymoma recurred. She had persistent hypogammaglobulinemia and multiple opportunistic infections. Conclusion: In MG patient under B cell depletion therapy had thymoma relapse, Good's syndrome may induce prolonged B cell depletion, hypogammaglobulinemia and opportunistic infections.